Clinical Psychology and Amyotrophic Lateral Sclerosis - Pagnini, Francesco; Rossi, Gabriella; Lunetta, Christian; Banfi, Paolo; Corbo, Massimo (Frontiers in Psychology, 2010)
Amyotrophic Lateral Sclerosis is a fatal and progressive disease, characterized by progressive muscles weakness, with consequent loss of physical capacities. Psychologists can play an important role in ALS care, by providing clinical activities in every step of the disease, including support and counseling activities directed to patients, their caregivers and to physicians.